Common sources and needs of weather information for rice disease forecasting and management in coastal Bangladesh. Issue 1 (31st December 2023) - Mousumi, Moriom Akter; Paparrizos, Spyridon; Ahmed, Md. Zafar; Kumar, Uthpal; Uddin, Md. Ektear; Ludwig, Fulco
ABSTRACT: Rice farmers in coastal Bangladesh are severely affected by climate change. Climate variability and change impact crop production in numerous ways, including by changing occurrences of different rice diseases. Weather and climate information services (WCIS) can assist farmers in improving agricultural decision-making, in relation to rice disease management. Currently, however, farmers in coastal Bangladesh have limited access to accurate, timely, and location-specific information on weather and climate. To design actionable information services, it is important to know the types of information that farmers need. With this in mind, the current research addressed three questions: (i) What types of weather information do coastal farmers need to forecast rice diseases? (ii) What types of weather information are currently available to coastal farmers? (iii) How does weather information play a role in rice disease management-related decision-making? Results indicate that coastal rice farmers have access to weather and climate information services mainly through personal experiences, neighbouring farmers, agricultural extension agents, local knowledge and input dealers. During interviews, farmers indicated that they mainly needed information on temperatures, rainfall, relative humidity, cloud cover, fog and wind information to predict rice disease outbreaks sufficiently in advance. Raising awareness about application of climate information services in rice disease management and building the capacity of farmers through training and education is vital to address major challenges faced by the coastal farmers in accessing weather information. We conclude that the farmers need more accurate, timely, location-specific, trustworthy and actionable weather information services to forecast and manage rice diseases.